La música como recurso pedagógico para el fortalecimiento de la creación poética - Japón Poma, Royme Germán (2024)
The study of music and its implications in learning within the field of language and literature has allowed it to be considered a pedagogical resource because it helps students develop their linguistic skills, especially writing. However, its use at the high school level is nonexistent, which devalues its pedagogical-motivational potential for students who experience difficulties in poetic creation. Therefore, the objective of this research is to analyze the contribution of music as a pedagogical resource for strengthening the poetic creation of second-year BGU students at the Unidad Educativa Gonzanamá. The study employs a mixed-methods approach, applying a survey that consisted of a diagnostic test, which allowed for quantifying the level of performance in poetic creation among the twenty-three students, and an interview with a teacher. The results showed that there are difficulties in writing, as well as a lack of extrinsic motivation to overcome these difficulties. This led to the design of a workshop based on music as a pedagogical resource for strengthening poetic creation in students. It concluded that among the benefits of the workshop are motivation, both for students, who achieve an adequate level of poetic creation, and for teachers, as music allows teaching to be innovative and more dynamic. It was recommended that teachers implement the workshop at any time during the school year, with the flexibility to adapt the activities to the needs of the student group and the genre of music used.